2017
DOI: 10.1007/s11146-017-9607-2
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Geographic and Cultural Dispersion on Information Opacity

Abstract: This paper investigates the influences of intrafirm geographic and cultural dispersion, the distance between the location of a firm's investments and its headquarters, on the firm's information environment. Specifically, using a sample of publicly traded real estate companies across the Asia-Pacific region, we examine how intrafirm geographic and cultural distance impacts a firm's capital acquisition costs. As a consequence of both the heavily regulated operating environment faced by these firms, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
1
2
0
Order By: Relevance
“…More specifically, our finding on the factors driving CSR in pharmaceutical companies is consistent with the study by Droppert and Bennett (2015), in which reputation benefits and long-term financial returns are the most encouraging factors [21]. As far as the differences found regarding the encouraging and discouraging factors for CSR in the medical equipment and biotechnology companies, this may be due to variations related to their size, field of operation, high competition and decision-making process [10,20,[51][52][53][54][55][56][57][58].…”
Section: Discussionsupporting
confidence: 87%
“…More specifically, our finding on the factors driving CSR in pharmaceutical companies is consistent with the study by Droppert and Bennett (2015), in which reputation benefits and long-term financial returns are the most encouraging factors [21]. As far as the differences found regarding the encouraging and discouraging factors for CSR in the medical equipment and biotechnology companies, this may be due to variations related to their size, field of operation, high competition and decision-making process [10,20,[51][52][53][54][55][56][57][58].…”
Section: Discussionsupporting
confidence: 87%
“…Also, studies conducted in the USA, Korea, Spain, and India [12] [32] [33] [34] showed that companies made donations of medicinal and protective products during the pandemic and implemented targeted CSR policies, mainly focused on the reinforcement of public health awareness and the stable relationships with stakeholders in order to address the COVID-19 effects and respond to the existing societal needs. Furthermore, several studies have reported that parent-subsidiary companies and geographic distance are factors related with barriers to the CSR performance [35] [36] [37]. Thus, our finding that national companies are more flexible in CSR decision making than the multinational ones, constitutes another similarity.…”
Section: Discussionmentioning
confidence: 52%
“…In this paper, we apply the commonly adopted metrics—the Hofstede’s six culture dimensions—to quantify the difference in cultural aspects between countries. The Hofstede’s six culture dimensions are comprised of the power ( PO ), the uncertainty avoidance ( UA ), the individualism/collectivism ( IC ), the masculinity/felinity ( MF ), the long-term orientation ( LT ), and the indulgence/restraint ( IR ) (Cashman et al, 2019 ; S. (Sam) Huang & Crotts, 2019; Jiang et al, 2018 ). In this paper, we use the absolute difference of the cultural indicators to quantify the cultural difference between countries.…”
Section: Methodsmentioning
confidence: 99%